Use of PVC pipes to determine bulk density for irrigation management - Matsinhe, Daniel; Pereira, Silvio; Oliveira, Rubens; Assis, Igor; Oliveira, Reginaldo (Revista Ciência Agronômica, 2018)
Irrigation has a great importance in the production of food, and it is responsible for consuming a large part of the water used by human activities. This makes the rational management of water use fundamental for sustainable food production. For this purpose, the determination of bulk density is important and needs to be obtained with the simplest, least onerous methods possible, while maintaining precision and accuracy. Therefore, the objective of this work was to evaluate the use of PVC pipes of different dimensions to determine bulk density. For comparison purposes, the volumetric ring, paraffin clod, beaker and excavation methods were also used. Deformed and undisturbed soil samples of different granulometries were collected at the depths of 0.025-0.075, 0.050-0.100, 0.075-0.125 and 0.100-0.150 m. The PVC pipes had diameters of 0.040, 0.050, 0.060 and 0.075 m and heights of 0.10, 0.15, 0.20 and 0.25 m. The bulk density results for each PVC pipe dimension were compared with those of the traditional methods by the unpaired t-test at 5% significance. For soils with a clayey or very clayey texture, the 0.040 m diameter and 0.15 m high PVC pipe presented the best results, with values closer to those of the standard method. For soils with a medium and sandy texture, the best results were found when a PVC pipe with a diameter of 0.060 m and a height of 0.15 m was used.